THE PROBLEM OF STUDYING LEADING CHARACTERS IN ENGLISH AND UZBEK FAIRY TALES (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
In the fairy tales of the peoples of the world, the leading characters are often the main characters. In most cases, the name of the fairy tale is named after them. This situation can be observed in the fairy tales of all nations. In fairy tales, the victory of good over evil, goodness over evil, is revealed mainly through the medium of leading characters. In this, he is unexpectedly helped by a creature or person from nowhere.